2018
DOI: 10.1093/restud/rdy006
|View full text |Cite
|
Sign up to set email alerts
|

Carry-Along Trade

Abstract: Large multi-product firms dominate international trade flows. Using novel linked production and export data at the firm-product level, we find that the overwhelming majority of manufacturing firms export products that they do not produce. Three quarters of the exported products and thirty percent of export value from Belgian manufacturers are in goods that are not produced by the firm, so-called Carry-Along Trade (CAT). The number of CAT products is strongly increasing in firm productivity while the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 43 publications
6
51
0
Order By: Relevance
“…Our model features large firms competing strategically when the demand features one-way complementarity between goods and services. This mechanism is also in line with Bernard et al (2017a) who show that the size of firm-level product scope allows firms to raise their price conditional on the quantity sold. Our theory can be seen as one of the ways to micro-found demand-scope complementarities behind the "carry along" trade phenomenon they emphasize, i.e.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our model features large firms competing strategically when the demand features one-way complementarity between goods and services. This mechanism is also in line with Bernard et al (2017a) who show that the size of firm-level product scope allows firms to raise their price conditional on the quantity sold. Our theory can be seen as one of the ways to micro-found demand-scope complementarities behind the "carry along" trade phenomenon they emphasize, i.e.…”
Section: Introductionsupporting
confidence: 83%
“…Third, Table A-4 in the Appendix shows that the sales premium associated with the provision of services is much stronger for the core product than for the fringe products of the firm; hence, there is substantial heterogeneity in the positive correlation between goods sales and services provision across the products in the bi-exporters' product portfolio. That the correlation between goods sales and services provision is much stronger for the main product, suggests that the fringe products may be themselves complements of the core product (Bernard et al, 2017a;Eckel and Riezman, 2016). the products they export to products for which they have a relatively lower productivity.…”
Section: Further Empirical Regularitiesmentioning
confidence: 99%
“…Blonigen (2016) examined the downstream effects of industrial policy in the steel sector. Finally, several studies in international trade have now shown that gross trade flows do not necessarily reflect the domestic production underlying the trade flow but value added is more appropriate (Koopman et al, 2014;Bernard et al, 2017). 8 In line with these studies we also focus on value added rather than gross export flows.…”
mentioning
confidence: 89%
“…On the contrary, the variable capturing trade diversion reduces imports from outside by 2.9% but is not significant across different econometric specifications, suggesting that trade diversion is rather small. 8 Bernard et al (2017) empirically show that many products shipped by manufacturing firms are not produced in-house, but are "carry-along trade", i.e. gross export sales are much larger than the domestic production shipped.…”
mentioning
confidence: 99%
“…Although the TradeStat is a very rich and unique data source, it still has some limitation. For example, there is no explicit information whether the firms that import these intermediate inputs only are acting as middlemen, that is carry‐along trade (Bernard, Blanchard, Beveren, & Vandenbussche, ), or that the firms are engaged in outward processing, that is the imported inputs are re‐exported to further processing abroad (Feenstra & Hanson, ). However, concentrating on firms within manufacturing industries only, the firms with main purpose to distribute these materials at a final destination are by definition excluded.…”
Section: Data Description and Estimation Strategymentioning
confidence: 99%